Pair production of neutral Higgs particles in the B-LSSM. (1st August 2022) - He, Dan; Feng, Tai-Fu; Yang, Jin-Lei; Ning, Guo-Zhu; Zhang, Hai-Bin; Dong, Xing-Xing
Abstract: Higgs pair production provides a unique handle for measuring the strength of Higgs self interaction and constraining the shape of the Higgs potential. Including radiative corrections to the trilinear couplings of CP -even Higgs, we investigate the cross section of the lightest neutral Higgs pair production in gluon fusion at the Large Hadron Collider in the supersymmetric extensions of the standard model. Numerical results indicate that the correction to the cross section is about 11% in the B-LSSM, while is only about 4% in the MSSM. Considering the constraints of the experimental data of the lightest Higgs, we find that the gauge couplings of U (1) B – L and the ratio of the nonzero vacuum expectation values of two singlets also affect strongly the theoretical evaluations on the production cross section in the B-LSSM.